THE DIVERSITY AND DISTRIBUTION OF TWO FAMILIES OF SUMATRAN LAND SNAIL (GASTROPODA: CAMAENIDAE AND CYCLOPHORIDAE) - Nova Mujiono; Windra Priawandiputra; Tri Atmowidi (BERITA BIOLOGI, 2019)
The diversity of land snail in Sumatra, Indonesia was firstly studied by Bock (1881), followed by some comprehensive studies by Degner (1928), Van Benthem Jutting (1959), and recently by Marwoto (2016). This research aimed to update the data on diversity and distribution of those two families, documenting new information on their distribution, make historical records of species occurrence, list species occurrence from inside and outside the conservation area. We collected primary data from 274 numbers of museum collections and secondary data from 29 literatures. In total, 58 species of Camaenidae and 66 species of Cyclophoridae were known from Sumatra. Fourteen land snail species, seven from family Camaenidae and seven from family Cyclophoridae, were added to the previous list of land snail species in Sumatra. There were 30 land snail species with new distribution ranges.